2015
DOI: 10.1007/s10120-014-0455-y
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein on postoperative day 3 as a predictor of infectious complications following gastric cancer resection

Abstract: Background Postoperative infectious complications (PICs) after gastric cancer resection remain a clinically relevant problem. Early detection of PICs, before critical illness develops, may be of considerable clinical benefit. The aims of this study were to investigate the predictive factors for PICs and to define the clinical parameters for detecting them early in patients with gastric cancer resection. Methods Clinical data for 417 consecutive patients undergoing elective gastrectomy for primary gastric cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 36 publications
3
66
0
Order By: Relevance
“…Nevertheless, increasing evidence shows that postoperative CRP level, as a risk factor for postoperative inflammation, can be used to predict complications after gastrectomy[7,24]. For instance, Kim et al[16] found that the CRP level on POD 4 was one of the most reliable predictors for complications following gastric cancer resection, when compared to many systematic inflammatory markers (white blood cells, neutrophils, platelet counts and CRP on POD 1).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, increasing evidence shows that postoperative CRP level, as a risk factor for postoperative inflammation, can be used to predict complications after gastrectomy[7,24]. For instance, Kim et al[16] found that the CRP level on POD 4 was one of the most reliable predictors for complications following gastric cancer resection, when compared to many systematic inflammatory markers (white blood cells, neutrophils, platelet counts and CRP on POD 1).…”
Section: Discussionmentioning
confidence: 99%
“…Post‐operative CRP was considered as a suitable post‐operative predictor for complications of curative (R0) gastrectomy in previous study . In this work, receiver operating characteristic curve was performed to compare the predictive accuracy of CRP on POD 3 and ΔALB for post‐operative complications.…”
Section: Resultsmentioning
confidence: 99%
“…Classical inflammatory markers such as CRP is demonstrated that is an important predictor for post‐operative complications after gastrectomy . Shishido et al .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] As a type of acute-phase protein with a short half-life (*19 h), CRP functions as an early defense against infection in innate immunity. Several groups have reported that high CRP levels on postoperative day (POD) 3 or 4 show superior diagnostic accuracy for the prediction of postoperative complications after gastrectomy.…”
mentioning
confidence: 99%
“…Several groups have reported that high CRP levels on postoperative day (POD) 3 or 4 show superior diagnostic accuracy for the prediction of postoperative complications after gastrectomy. 4,8 Others have devised a CRP-based nomogram incorporating the CRP level on POD 3, patient comorbidities, Eastern Cooperative Oncology Group (ECOG) performance status, and operative time to predict a patient's risk for a major complication after laparoscopic gastrectomy. 9 What these studies (and many similar studies) share in common is the use of either a single laboratory value or some combination of laboratory and clinical variables designed to predict a complicated postoperative course.…”
mentioning
confidence: 99%